(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: To describe the prevalence of burnout syndrome and factors showing potential associations among Medical staff at the National Institute of Mental Health in 2025. Methods: A cross-sectional study was conducted on 71 healthcare workers. The MBI-HSS was used to assess emotional exhaustion, depersonalization, and reduced personal accomplishment. Descriptive statistics and association tests were applied, with statistical significance set at p < 0,05. Results: The prevalence of burnout was 25.4%. High levels of emotional exhaustion, depersonalization, and reduced reduced personal accomplishment were found in 4.2%, 22.5%, and 25.4% of participants, respectively. Several occupational characteristics - including female sex, ≥ 60 working hours per week, ≥ 5 night shifts per month, and lower perceived support from supervisors or colleagues - demonstrated a tendency toward association with burnout, although none reached statistical significance. Conclusion: Burnout among medical staff at the National Institute of Mental Health is noteworthy, particularly regarding depersonalization and reduced personal accomplishment. Although no examined factor showed significant associations, observed trends highlight the need for organizational strategies to reduce workload and strengthen psychosocial support.